Essentials of English: A practical handbook covering all the rules of english grammar and writing style - Hopper, Vincent F. et. al. (Washington (State) : BARRON`S, 2000)
It reviews English grammar, sentence structure, punctuation, and correct word usage.
1. Personal pronouns 2. Fuctions of Possessives
incluye índice
Col. Educ
Keywords: 1. THE PRONOUN 2. THE VERB